AFRICA AND THE ‘GLOBALIZATION BARGAIN’: TOWARDS A COLLECTIVE ECONOMIC SOVEREIGNTY - Okoli, Al Chukwuma; Atelhe, Atelhe George (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
Africa’s existential situation in the prevailing global order is such that no state thereof can afford to take national sovereignty too seriously. Apart from the myriad of structural challenges imposed on the continent by globalization, Africa is faced with a gamut of political and economic problems that can only be meaningfully addressed through some form of strategic multilateral collaboration. Africa’s aspiration to economic sovereignty has been constrained by the structural conditionalities of globalization, which have kept the continent overly weak, dependent and underdeveloped. The constraint is so immanent that individual African states can hardly afford even the relative sovereignty to harness a strategic balance in the fast ossifying asymmetries of interdependence that characterize the contemporary global political economy. It is posited in this paper that the remedy for Africa lies in the ability of her states to transcend their disempowering territorial-cum-nationalistic divides and capitalize on the existing continental multilateral mechanisms towards mainstreaming collective sovereignty, based on the principle of pan-African supranationalism. To that end, leveraging and maximizing the gains and prospects of extant regional and continental supranational organisms would become both salient and expedient.